The transvaginal hybrid NOTES versus conventionally assisted laparoscopic sigmoid resection for diverticular disease (TRANSVERSAL) trial: study protocol for a randomized controlled trial - Senft, Jonas; Warschkow, René; Diener, Markus K.; Tarantino, Ignazio; Müller, Beat P.; Linke, Georg R. (Trials, 2014)
Background: Natural orifice transluminal endoscopic surgery (NOTES) is the consequence of further development of minimally invasive surgery to reduce abdominal incisions and surgical trauma. The potential benefits are expected to be less postoperative pain, faster convalescence, and reduced risk for incisional hernias and wound infections compared to conventional methods. Recent clinical studies have demonstrated the feasibility and safety of transvaginal NOTES, and transvaginal access is currently the most frequent clinically applied route for NOTES procedures. However, despite increasing clinical application, no firm clinical evidence is available for objective assessment of the potential benefits and risks of transvaginal NOTES compared to the current surgical standard. Methods: The TRANSVERSAL trial is designed as a randomized controlled trial to compare transvaginal hybrid NOTES and laparoscopic-assisted sigmoid resection. Female patients referred to elective sigmoid resection due to complicated or reoccurring diverticulitis of the sigmoid colon are considered eligible. The primary endpoint will be pain intensity during mobilization 24 hours postoperatively as measured by the blinded patient and blinded assessor on a visual analogue scale (VAS). Secondary outcomes include daily pain intensity and analgesic use, patient mobility, intraoperative complications, morbidity, length of stay, quality of life, and sexual function. Follow-up visits are scheduled 3, 12, and 36 months after surgery. A total sample size of 58 patients was determined for the analysis of the primary endpoint. The confirmatory analysis will be performed based on the intention-to-treat (ITT) principle. Discussion: The TRANSVERSAL trial is the first study to compare transvaginal hybrid NOTES and conventionally assisted laparoscopic surgery for colonic resection in a randomized controlled setting. The results of the TRANSVERSAL trial will allow objective assessment of the potential benefits and risks of NOTES compared to the current surgical standard for sigmoid resection. Trial registration: The trial protocol was registered in the German Clinical Trials Register (DRKS00005995) on March 27, 2014.
Gesehen am 28.07.2020